Pelatihan Pembelajaran Berbasis Self-Regulated Learning bagi Guru Bahasa Inggris SMPN Kota Banjarmasin: Training on Self-Regulated Learning-Based Instruction for Junior High School English Teachers in Banjarmasin - Sutiono, Cayandrawati; Triana, Novita; Arapah, Elvina; Kamal, Sirajuddin; Muth'im, Abdul; Jumariati, Jumariati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
English language learning as a foreign language in Indonesia is often hindered by students' low motivation to learn independently. The concept of self-regulated learning (SRL), which emphasizes students' ability to manage their own learning, can be a potential solution to overcome this problem. However, teachers' understanding of the SRL concept is still minimal. This community service activity in the form of training aims to improve the knowledge and skills of English teachers in Banjarmasin city related to SRL. The community service activity was conducted by the PDWA Team of the English Education Study Program, FKIP, Lambung Mangkurat University. It was conducted over two days, covering the exposition of SRL concepts and strategies, as well as the design of SRL-based learning plans. The participants were 35 teachers from 35 SMPN in Banjarmasin who are members of MGMP Bahasa Inggris. The results showed a high level of interest and awareness among participants in developing SRL-based English language learning to increase students' motivation and active participation in the learning process. Thus, it can improve students' English proficiency. Several follow-up suggestions are proposed, including forming an SRL practitioner community, developing SRL-based learning materials, providing follow-up training, and collaborating with relevant parties.